MICROSTRUCTURAL BRAIN ABNORMALITIES AND SYMPTOM DIMENSIONS IN CHILD AND ADOLESCENT PATIENTS WITH OBSESSIVE‐COMPULSIVE DISORDER: A DIFFUSION TENSOR IMAGING STUDY. Issue 12 (28th November 2014) - Lázaro, Luisa; Calvo, Anna; Ortiz, Ana G.; Ortiz, Ana E.; Morer, Astrid; Moreno, Elena; Calvo, Rosa; Bargallo, Núria
<x xml:space="preserve">Abstract</x> Background The aims of this study were to determine white matter (WM) microstructure abnormalities in obsessive‐compulsive disorder (OCD) using diffusion tensor imaging, and to investigate whether these abnormalities differ according to OCD symptom dimensions. Methods Sixty‐three child and adolescent OCD patients (11–18 years old) and 37 healthy subjects matched for gender, age, and estimated intelligence quotient were assessed by means of psychopathology scales and diffusion tensor magnetic resonance imaging. Results Compared with healthy controls OCD patients showed a significant decrease (t = 3.79, P = .049 FDR‐corrected) in fractional anisotropy (FA) in the anterior region of the corpus callosum (CC). In addition, mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) values were significantly increased in OCD compared with controls in the CC and in several WM regions of the cingulate, frontal and occipital lobes, basal ganglia, cerebellum, and pons. Compared with healthy controls, OCD patients presenting the harm/checking dimension showed decreased FA in the CC and in the left anterior cingulate gyrus and caudate nucleus, whereas patients with a predominant contamination/washing symptom dimension presented significantly decreased FA in the left midbrain, lentiform nucleus, insula, and thalamus, and increased MD, AD, and RD in both the anterior lobes of cerebellum and in the pons. Conclusions The findings suggest WM abnormalities at the microstructural level in the pathogenesis of OCD. Moreover, WM abnormalities in OCD may vary according to the specific OCD symptom dimensions, thus indicating the clinical heterogeneity of the condition.